Analisis Kinerja Dewan Perwakilan Rakyat Daerah (DPRD) Dalam Mengawasi Masyarakat Yang Terdampak Covid-19 di Kota Medan - Fara Sofia Ashari; Marliyah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
DPRD is an institution that has a supervisory function, a budget function and a legislative function. Therefore, this study intends to determine the performance of DPRD in supervising the people in the city of Medan. There are many problems related to the Covid-19 outbreak in the world, including Indonesia. It is not only the DPRD that has the responsibility in dealing with Covid-19 but also all components of the nation. The approach in this study uses a qualitative approach. The source of this research data is secondary data. Secondary data in this study was obtained by understanding the literature, the results of reviews from previous researchers, books, journals and from other sources related to the subject matter. The results of this study are performance, its performance is only seen as an appeal so that people do not leave the house and just stay at home. From the loss of a job to the loss of income, the people of Medan City feel. Furthermore, the anomalies that occur indicate acts of corruption. The government promised such assistance to the community but it did not arrive. There was also data on people affected by Covid-19 who received assistance not included in the data.